Urgensi Layanan Penelusuran Untuk Mahasiswa Skripsi Di Perpustakaan Perguruan Tinggi - Indah Wijaya Antasari (THE LIGHT : Journal of Librarianship and Information Science, 2021)
The Final Student (S1 level) of UIN Saifuddin Zuhri, has the final assignment in research /thesis. The academic library provides services related to student information about thesis assignments. This research aims to find out the views of students in semester seven and above about the importance of special library services for final-level students—research methods through descriptive qualitative approaches, with data retrieval through interviews and documents. This research will be interviews conducted in two stages; first, in Five students researching their thesis and students who have just graduated; Second, the question is open to 99 students in semester seven and above. The results showed that the first stage, information retrieval service as a unique service for thesis students, is very needed. However, some students do not encounter obstacles in completing their thesis but still consider if information retrieval service is necessary. The second stage, open question answers to 99 students, showed that special services for thesis students were indispensable. Student complaints include difficulty finding referrals and a lack of knowledge about compiling a good thesis. In conclusion, the college library has demanded that final-level students hold special services for thesis students. The services provided should be with sufficient officers, in this case, adjusted to the number of students who are thesis.